The Activity of the Kogon Food Special Supply Department during the Years of the War against Fascism (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article analyzes the development of industry in the Bukhara region during the Second World War, efforts to support the front, as well as opinions about plants and factories transferred to the territory of Bukhara during the war.